The Influence Between Facebook Malaysia: Fashionvalet Vs Zalora - Norashiddin, Faris Aizat (2022)
The purpose of this study is to examine the influence of the type of content post on online engagement in the chosen e-retailer fashion companies Facebook pages which are FashionValet and Zalora.